Competitive policy, trade and development in the Common Market for Eastern and Southern Africa (COMESA) : the relevance of regional integration, international cooperation and the contribution of competiion policy to development in COMESA countries (UN GenevaCH, 2000)
Includes papes presented at the Regional Seminar of Competition Policy, Trade and Development held in Lusaka, Zambia 3-4 June 1999 as well as papers presented at the National Seminar on Competition Law and Policy held in Lusaka, Zambia 31 May-2 June 1999.
Keywords: COMPETITION POLICY